Education at the Cultural Crossroads: Navigating Identity and Globalization in Southeast Asia - Fahruddiana, Yosphia (PT. BATARI EDU CALYA, 2025)
This study explores the role and challenges of education in navigating the cultural dynamics of identity in Southeast Asia amid the forces of globalization. Using a literature review approach, the article analyzes how educational systems in the region respond to rich cultural diversity, address the pressures of global homogenization, and facilitate the emergence of cultural hybridity in learning contexts. The main findings indicate that educational institutions in Southeast Asia serve as key arenas where negotiations between preserving local cultural heritage and adapting to global influences take place. Globalization poses significant challenges to curricula and pedagogy, particularly concerning the dominance of global languages and foreign cultural content, which may erode local uniqueness. However, adaptive efforts also exist, such as educational approaches that integrate traditional and global elements (hybridity), as well as the use of technology to promote local culture. This article emphasizes the urgency of educational policies that support cultural preservation through relevant curricula, teacher capacity building, and character education grounded in local values, while equipping students with global competencies. These insights are crucial for understanding how education can contribute to shaping the cultural identity of Southeast Asia's younger generation in an ever-evolving global landscape